KAJIAN POTENSI LAJU RESAPAN ALAMI PADA ZONA TIDAK JENUH BATUAN GUNUNGAPI DI DAERAH BATU MALANG - (NIM 22198504), Sufiyanto
Abstrak : Batu area have high rainfall and geologycal as quarterner volcano area which is dominated by rock result destruction volcano, breccia, rock sand and tuff as characteristic of good rainfall penetration area. The aim of this research is to analyzed natural infiltration rate potential and to discuss, several effect. Natural rate penetration potential can be approach by two method, namely water scale and directly measurement with double ring infiltrometer at 16 points which determined as randomly. Several factors was concerned for determine its effect on last infiltration rate as dependent variable is soil physical properties (sand, silt, clay percentage), inclination slope and landscape cover as independent variable. Water scale analysis product infiltration volume 116,2 x 106 m3/year. While from double ring infiltrometer measurement is 100,9 x 109/year. There are factor cause this differences, such as assumption was taken in this water scale calculations rough, while in infiltration assumption taken that soil surface always stagnant water, which regardless evapotranspirations and inclination slope. Last rate infiltration measurement with double ring infiltrometer in research area varies from 0,06-0,83 cm/minute. The rate infiltration average value is 0,361 cm/minute. Study about independent variable effect to dependent variable analyzed by double linear regression method_ Correlation between last rate infiltration and soil heterogenity which is indicated by sand thickness (+0,782), and silt (-0,484) is very significant with significantly 0,029 and 0,2744 respectively. The other variable with adequate significant is landscape cover (+0,427) with significantly 0,05.